Příčiny neúspěchu stabilizace Jižního Vietnamu od nástupu Johnsona po podpis mírové smlouvy roku 1973 - Koreček, Janis (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2010)
This bachelor thesis deals with the United State's engagement in the Vietnam War. Time became limited under the Johnson and Nixon administration. The primary target of this thesis is to gather main reasons for why South Vietnam was unable to be established as an independent and modern state as had both South Korea and Japan in the past. There are significances under the Nixon and Johnson administration. Both had been tight with the US legislative process and were able to narrow their options of how to solve the stalemate in Vietnam. Johnson was more focused on domestic policy known as "Great Society". For Nixon, foreign policy was of more importance. Great discord came from Nguyen Van Thieu, South Vietnam's head of state, who never co-operated much with US administration. His region was more repressive than democratic and was one in which there was no connection between him and the South Vietneme inhabitants. The Army of South Vietnam played a special role. The conclusion describes the main motives of why South Vietnam ultimately failed.